2022
DOI: 10.2147/jir.s347161
|View full text |Cite
|
Sign up to set email alerts
|

Serum Albumin to Globulin Ratio is Associated with the Presence and Severity of Inflammatory Bowel Disease

Abstract: Objective Serum albumin to globulin ratio (AGR) is a marker of inflammatory disease, but its role in inflammatory bowel disease (IBD) remains unknown. The primary purpose of the present research was to explore the relationship between serum AGR and inflammatory bowel disease (IBD). Methods A total of 179 patients with ulcerative colitis (UC), 210 patients with Crohn’s disease (CD), and non-IBD controls (age- and gender-matched controls who have gastrointestinal (GI) sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…AGR has been evaluated in many inflammatory, autoimmune, and malignant diseases and its prognostic role determined in numerous previous studies. [13][14][15][16][17][18][19]26 However, we encountered no studies evaluating the relationship between AGR and IGM. In the present study, we investigated the role of AGR in patients with IGM for the first time in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AGR has been evaluated in many inflammatory, autoimmune, and malignant diseases and its prognostic role determined in numerous previous studies. [13][14][15][16][17][18][19]26 However, we encountered no studies evaluating the relationship between AGR and IGM. In the present study, we investigated the role of AGR in patients with IGM for the first time in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified low AGR values as a poor prognostic factor in solid cancers such as those of the esophagus, stomach, and colon, and nasopharyngeal cancers. [14][15][16][17] In addition, AGR is an inflammation-based index that has been shown to be capable of predicting the severity of inflammatory bowel diseases, 18 predicting the risk of developing lupus nephritis in patients with systemic lupus erythematosus. 19 However, the association between AGR and IGM recurrence has never been studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…Albumin and globulin, easily accessible and reliable biomarkers in the basic metabolic panel, have proven to be critical markers associated with inflammation and infection [ 34 , 35 ]. Albumin, a negative acute-phase reactant, is widely considered to be an inflammatory and nutritional biomarker in humans [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Albumin and globulin, easily accessible and reliable biomarkers in the basic metabolic panel, have proven to be critical markers associated with in ammation and infection. 29,30 Albumin, a negative acute-phase reactant, is widely considered to be a biomarker of in ammatory and nutritional condition of the human body. 31 Hypoalbuminemia is correlated with malnutrition, hepatopathy, kidney disease, and all kinds of in ammation.…”
Section: Discussionmentioning
confidence: 99%